2019
DOI: 10.1111/cob.12334
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of sick leave: A systematic review and meta‐analysis

Abstract: Summary Body mass index (BMI) is related to different health dimensions and can be a risk factor for diseases. Our objective was to systematically review and meta‐analysis the association BMI and the risk of sick leave. Four databases were searched for articles until late December 2018 and the results of the studies were extracted and combined using random effects methods. Several sub‐group analyses were conducted as well as bias of publication were measured. A total of 23 longitudinal studies entered into met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…7 12 13 Amiri have shown that workers who are overweight or obese have a 1.2 to 1.3 times higher risk of sick leave than workers with a healthy body weight. 7 Troelstra et al have reported that smoking is associated with a 31% increase in risk of sick leave. 13 Obesity and smoking are risk factors with respect to several diseases, including mental illness and cardiovascular disease, which are themselves risk factors for sick leave.…”
Section: Discussionmentioning
confidence: 99%
“…7 12 13 Amiri have shown that workers who are overweight or obese have a 1.2 to 1.3 times higher risk of sick leave than workers with a healthy body weight. 7 Troelstra et al have reported that smoking is associated with a 31% increase in risk of sick leave. 13 Obesity and smoking are risk factors with respect to several diseases, including mental illness and cardiovascular disease, which are themselves risk factors for sick leave.…”
Section: Discussionmentioning
confidence: 99%
“…This notion has received support from studies that found that individuals who suffer from obesity are more likely to take sick leave. 30–32 The main reasons for receiving the disability pension in Finland are mental disorders (52%) and musculoskeletal diseases (19%). 19 As obesity has been identified as a major risk factor for mental disorders [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An important mechanism, partly explaining education differences in health, is differences in health behaviors [ 9 , 12 ]. Knowledge about the influence of health behaviors on sickness absence is limited [ 13 19 ], but lifestyle or health behaviors have been documented as one explanation for socioeconomic differences in sickness absence [ 6 , 10 , 11 , 20 , 21 ]. The etiological processes underlying the association between education, health behaviors and sickness absence is poorly understood, but results from some studies indicate that these associations may be confounded by unobserved familial factors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of lifestyle or health behaviors for sickness absence has been studied to a limited degree only. Much of the evidence focuses on single health behaviors, is based on relatively small sample sizes and findings have been mixed [ 13 18 ]. However, a large observational study of cohorts from France, Finland, and the UK found that lifestyle-related factors including BMI, physical activity, smoking and alcohol consumption were all associated with sickness absence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%